Pengendalian Longsor di Daerah Desa Sumberharjo, Kecamatan Prambanan, Kabupaten Sleman, Daerah Istimewa Yogyakarta - Dian Hudawan Santoso; Eni Muryani; Adilla Zahra Permatasari (LPPM Universitas Mataram, 2019)
The landslide occurred in area of Sumberharjo Village, Prambanan Subdistrict, Regency of Sleman, Daerah Istimewa Yogyakarta Province on 28th November 2018.The landslide area have a steep slope and complex geological conditions like a cracks. The closest settlement is located 8m far from the landslide area. The purpose of the research is to determine the vulnerability of landslide zonation level based on control and trigger factor and to design technique of controlling landslide area.The methodology used in this research are survey method and field mapping. Mapping method based on the control factor which has parameter like slope, soil texture, soil thickness, weathering of rock, infiltration capacity and land use. The rainfall level parameter as a trigger factor are analyzed by secondary data. Vulnerability of landslide zonation level zoning is obtained by the scoring method based on these parameters. Determination of slope engineering by taking 3 samples of soil for laboratory analysis. The soil sampling technique is purposive sampling which is based on slope and soil texture in landslide area. The laboratory results are used to calculate slope stability using the Janbu Method. All data obtained are analyzed based on environmental conditions. The research area has 3 landslide vulnerability zones: low vulnerability level with 2756,18 m2 of area, moderate vulnerability level with 61556,92 m2 of area, and high vulnerability level with 6298,90 m2 of area. The value of safety factor on landslide area is 0.94 which is classified as unstable. Lanslide management applied in area which has high vulnerability level on landslide area by making a bench that combined with gravity wall, surface drainage, and vegetation planting such as Jati and vertiver grass. The control effort increases the value of the slope safety factor to 1.33